Effects of perturbation or plyometric training on core control and knee joint loading in women during lateral movements - Weltin, E.; Gollhofer, A.; Mornieux, G. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Deficits in trunk control are argued to increase the risk of knee injuries. However, no existing training program effectively addresses trunk control during lateral movements, such as cutting maneuvers. The purpose of this study was to investigate whether a combination of perturbation and plyometric training (PPT) would reduce trunk excursions against the new movement direction and reduce knee joint moments during lateral movements. Twenty-four active women participated in a RCT, where trunk and pelvis kinematics and knee joint moments were measured during lateral reactive jumps (LRJ) and unanticipated cutting maneuvers before and after a 4-week PPT program and compared to a control group. During LRJ, trunk rotation away from the new movement direction was reduced (P < 0.001), while pelvis rotation toward the new direction was increased (P = 0.006) after PPT. Moreover, decreased knee extension moments (P = 0.028) and knee internal rotation moments (P < 0.001) were reported after both trainings. Additionally, PPT reduced trunk rotation by 7.2° during unanticipated cuttings. A 4-week PPT improved core control by reducing trunk rotation and reduced knee joint moments during LRJ. During training, perturbations should be introduced to improve core control during dynamic athletic movements, possibly reducing the risk of ACL injuries.